Theoretical Study on Open‐Shell Singlet Character and Second Hyperpolarizabilities in Cofacial π‐Stacked Dimers Composed of Weak Open‐Shell Antiaromatic Porphyrins. Issue 21 (20th September 2018) - Fujiyoshi, Jun‐Ya; Tonami, Takayoshi; Yamane, Masaki; Okada, Kenji; Kishi, Ryohei; Muhammad, Shabbir; Al‐Sehemi, Abdullah G.; Nozawa, Ryo; Shinokubo, Hiroshi; Nakano, Masayoshi
Abstract: From the analysis based on the broken‐symmetry density functional theory (DFT) calculations, we in this study propose a strategy to enhance the open‐shell characters and third‐order nonlinear optical (NLO) properties of π‐stacked dimers composed of antiaromatic molecules with weak open‐shell characters. For this purpose, we here constructed cofacial π‐stacked dimer models composed of aromatic and antiaromatic Ni II porphyrins in order to examine the π‐π stacking distance ( R ) dependence of the diradical characters ( y ) and static second hyperpolarizabilities (γ). The antiaromatic porphyrin dimers are found to have intermediate y around R ∼3.3 Å, the result of which originates in the unique intermolecular interactions between the antiaromatic monomers. Static γ along the stacking direction of such antiaromatic porphyrin dimers with intermediate diradical characters are shown to be enhanced significantly as compared to those of the isolated monomers and the aromatic porphyrin dimers. Abstract : Open‐shell electronic structures and third‐order nonlinear optical (NLO) properties of face‐to‐face π‐stacked dimers composed of weak open‐shell antiaromatic porphyrins are investigated. Owing to the unique intermolecular interactions, the antiaromatic porphyrin dimers have intermediate diradical characters around the stacking distance of R ∼3.3 Å where their third‐order NLO properties are significantly enhanced.